Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1177/089875640902600107
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Gingival Contour Plaque Index: Six-Month Plaque and Gingivitis Study

Abstract: The Gingival Contour Plaque Index (GCPI) is a recently introduced and validated method of measuring plaque accumulation in dogs. It focuses on plaque accumulated along the gingival margin. Plaque accumulation in this area leads to gingival inflammation and, potentially, periodontitis. A 6-month plaque and gingivitis study was conducted to demonstrate the clinical research application of the GCPI, and to ensure that documented quantification of plaque-reducing efficacy could be related to a reduction in gingivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Routine methods include the modified Logan and Boyce plaque index which is used to quantify plaque accumulation on the buccal surface of the whole tooth 20 and the gingival contour plaque index (GCPI), which focuses on plaque that accumulates along the buccal gingival margin. 21,22 Both of these methods have been endorsed by the Veterinary Oral Health Council (VOHC; www.vohc.org) for supporting product claims relating to plaque control. In vivo product efficacy trials require a clean mouth model, where cats or dogs are anesthetized at the start of the study and at the end of each test phase so the teeth may be scaled and polished.…”
Section: Introductionmentioning
confidence: 99%
“…Routine methods include the modified Logan and Boyce plaque index which is used to quantify plaque accumulation on the buccal surface of the whole tooth 20 and the gingival contour plaque index (GCPI), which focuses on plaque that accumulates along the buccal gingival margin. 21,22 Both of these methods have been endorsed by the Veterinary Oral Health Council (VOHC; www.vohc.org) for supporting product claims relating to plaque control. In vivo product efficacy trials require a clean mouth model, where cats or dogs are anesthetized at the start of the study and at the end of each test phase so the teeth may be scaled and polished.…”
Section: Introductionmentioning
confidence: 99%
“…The procedures used in this study demonstrated low intra-and inter-grader variability, and the computer derived coverage calculations correlated well to a human grader. The quantification of oral substrate accumulation using QLF derived images was able to demonstrate the ability of established dental diets 23,43 to inhibit oral substrate accumulation. This study differs from previous studies in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the importance of quantifying oral biofilm and the ability of specific technologies to reduce its accumulation, a diverse array of methods have been investigated, [11][12][13][14][15][16][17][18][19] including systems specific to dogs and cats. [20][21][22][23] These methods generally involve disclosing the dental plaque and then manually assessing coverage by assigning a score. One of the most common scoring systems used in clinical trials in pets is the Logan and Boyce index, originally introduced in 1994, and subsequently modified.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Each owner, animal, and its environment must be assessed on an individual basis to develop a treatment plan that is reasonable and attainable based on the unique circumstances of each case. 34,35 Dental disease starts at a young age and continues through the life of the animal, therefore prevention and treatment are important for quality of life and overall health. Plaque accumulation with a predominance of anaerobic organisms in this area leads to gingival inflammation and, potentially, periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Plaque accumulation with a predominance of anaerobic organisms in this area leads to gingival inflammation and, potentially, periodontitis. 34,35 Dental disease starts at a young age and continues through the life of the animal, therefore prevention and treatment are important for quality of life and overall health. 36,37 A non-toxic, low viscosity, barrier sealant was developed to be applied subgingivally as a liquid, drying quickly to form a hydrophilic barrier film.…”
Section: Introductionmentioning
confidence: 99%